Correlation and Path Coefficient Analysis for Seed Yield and Yield Components in Chickpea under Rainfed Condition - Hama, Shara Jala (Journal of Kerbala for Agricultural Sciences, 2019)
Chickpea is rich in protein and micronutrients and plays a significant role in human diet especially as accompaniment to staples, but seed yields in Kurdistan are still below the crop potential. This investigation was conducted during the spring seasons of 2017, at Bakrajo Research Station, College of Agricultural Sciences/University of Sulaimani to determine relationships among yield and some yield components using correlation and path coefficient analysis in chickpea grown under rainfed conditions. The character seed yield showed positive and highly significant correlation with most characters including plant height, number of branches per plant, deep of roots, number of pods per plant, number of seeds per pod, 100 seed weight, dry mater weight, pod weight per plant, protein percentage and biological weight. Characters dry matter weight per plant recorded the highest positive direct effect on seed yield reached 0.848, while the maximum positive indirect effect on seed yield recorded by weight of pods per plant via dry matter weight per plant with 0.795.